The mortal God: imagining the sovereign in colonial India - Banerjee, Milinda (Cambridge University Press, 2018)
The Mortal God is a study in intellectual history which uncovers how actors in colonial India imagined various figures of human, divine, and messianic rulers to battle over the nature and locus of sovereignty. It studies British and Indian political-intellectual elites as well as South Asian peasant activists, giving particular attention to Bengal, including the associated princely states of Cooch Behar and Tripura. Global intellectual history approaches are deployed to place India within wider trajectories of royal nationhood that unfolded across contemporaneous Europe and Asia. The book intervenes within theoretical debates about sovereignty and political theology, and offers novel arguments about decolonizing and subalternizing sovereignty